Design of the usability measurement tool for multimodal mobile applications - Al-Aidaroos, Ahmed Sheikh Abdullah; Abdul Mutalib, Ariffin (Penerbit UTM Press, 2015)
Nowadays, mobile phones provide not just voice call and messaging services, but plethora of other services.Those computational capabilities allow mobile phones to serve people in various areas including education, banking, commerce, travelling, and other daily life aspects. Meanwhile, the number of mobile phone users has increased dramatically in the last decade.On the other hand, the usability of an application can usually be verified through the user interface. Therefore, this paper aims to design a measurement tool to evaluate the usability of mobile applications based on the usability attributes and dimensions that must be considered in the interface.To obtain the appropriate attributes, a Systematic Literature Review (SLR) has been conducted and the Goal Question Metric (GQM) has been used to design the tool. From 261 related works only 18 most relevant ones were selected, through four SLR. 25 dimensions were found through the SLR, but some of these dimensions are synonymous or a part of other dimensions. Consequently, three dimensions must be included in any usability evaluation instrument, which is broken down into ten sub dimensions.